LEKSIKON DAN GRAFEM BERDASARKAN VISUALISASI GAMBAR: KAJIAN PSIKOLINGUISTIK - Fidrayani (PrimEarly : Jurnal Kajian Pendidikan Dasar dan Anak Usia Dini, 2021)
There are two lexical problems in children, one of which is lexical mastery itself. The purpose of this research is to photograph the lexical picture possessed by children based on the visualization of images and conversations that are carried out during interactions. The research method uses a qualitative approach with observation and recording techniques. The subjects in this study were seven children located in three different locations. The results of lexical recording in general, children can pronounce correctly according to the meaning, although in some children it is still not in accordance with the meaning or the pronunciation. This is caused by environmental conditions and different children's lexical mastery